Comparison of the CMNC and MNC apheresis protocol for the collection of T‐cells showed comparable outcome: An observational study in a single centre. Issue 3 (21st February 2018) - Putensen, Daniel; Smith, Richard; Pilcher, Linda; Trandafir, George
ABSTRACT: Background: An increasing demand for human lymphocytes require an efficient, reliable and reproducible lymphocyte process. Here, we compare the Spectra Optia® CMNC protocol with the Optia MNC platform in unmobilised donor lymphocyte collections. Purpose: To establish and compare the feasibility, efficiency, and practicability of the two apheresis protocols. Methods: Data was collected prospectively from 60 non‐cytokine stimulate donors who underwent a total of 64 T‐cell collection procedures. Of these, 24 procedures were performed in the CMNC cohort and 40 procedures in the MNC cohort. All donors in the CMNC group were related; all donors in the MNC group were donors from a registry. Donor characteristics, procedure parameters and cellular product content were analysed and compared. Results: Donor characteristics and full blood count results were comparable, except the median white blood cell count, which was higher in the CMNC cohort (6.87 vs. 5.58 ×10 9 /L, P < .005). This resulted in higher lymphocyte (1.95 vs. 1.57 ×10 9 /L, P < .009) and CD3+ cell counts (1476 vs. 1060/L, P < .02). A total blood volume processed of 2.0 resulted in i) run time (222 vs. 242 min), ii) product volume (192 vs. 183 ml), iii) platelet content (2140 vs. 1345 ×10 6 /ml, P < .003). CD3+ CE2 (%): 54.7 vs. 50.4. Conclusion: The CMNC and MNC protocols are reliable, efficient and comparable in performance parameters and cell composition of final product, respectively. One advantages of the CMNC protocol is the potential ability to tailor the cell composition of the final product accordingly to demands from cell processing laboratories.